Evolving epigenomics of immune cells at single-nucleus resolution in children en route to type 1 diabetes - Pastinen, Tomi; Grundberg, Elin; Bradley, Todd; Honkanen, Jarno; Cheung, Warren A.; Vuorela, Arja; Johnston, Jeffrey J.; Yoo, Byunggil; Khanal, Santosh; McLennan, Rebecca; Ilonen, Jorma; Vaarala, Outi; et al. (Springer Science and Business Media LLC, 2026)
The appearance of diabetes-associated autoantibodies is the first detectable sign of the disease process leading to type 1 diabetes (T1D). Evidence suggests that T1D is a heterogenous disease, where the type of antibodies first formed implies subtypes. Here, we leverage longitudinal samples collected from 98 European TRIGR participants (49 children who subsequently presented with T1D, and 49 matched controls), and profile single-cell epigenomics at different time points of disease development. Quantitation of cell and nuclei populations, complemented by analysis of transcriptome and open-chromatin states, indicates robust, early, replicable monocyte lineage differences between cases and controls, suggesting the early emergence of heightened pro-inflammatory cytokine secretion among cases. The order of autoantibody emergence in cases shows variation across lymphoid and myeloid cells, potentially indicating divergence in the cellular immune response. The strong monocytic lineage representation in peripheral blood immune cells before seroconversion and the weaker differential coordination of these gene networks close to clinical diagnosis emphasize the importance of early life as a critical phase in T1D development.